Development of bamboo – rice husk ash and cement mixture for livestock house roofing sheets (2013)
The purpose of this research is to design, fabricate and install locally developed roofing sheets on a king post truss model of a livestock house using rice husk and bamboo fibers which are readily available in most Nigerian farms with some additions of cement to the mixture. The effects of ratios of Rice Husk Ash (RHA) and bamboo fibers on the impact strength, density, thickness swelling and water absorption were also investigated. The average density of the composite roofing sheet produced ranged from 1779 to 2197Kg/m3. The control test specimen density was 2376Kg/m3. The addition of pozollan decreased the density of the composite. Thickness Swelling (TS) values ranged from 0.07 to 5.97% at two hours and from 0.08 to 6.5% at 24 hours for different composition. The percentage water absorption (WA) by the composite was from 0.17 to 1.13% at 2 hrs while it was 0.21 to 1.43% at 24hrs. However further research would be carried out on the structure to determine the thermal comfort of the livestock to be kept in the building.